Age-related hearing loss was accelerated by apoptosis of spiral ganglion and stria vascularis cells in ApoE KO mice with hyperglycemia and hyperlipidemia - Nguyen, Phuong Thi Thanh; Song, Hayoung; Kim, Boyoung; Kim, Yoo Yeon; Kim, Chulho; Lee, Jun Ho; Suh, Jun Gyo (Frontiers in Neurology, 2022)
Age-related hearing loss (ARHL) is associated with diabetes and/or dyslipidemia in humans. However, the detailed mechanism for the development of ARHL by diabetes and/or dyslipidemia has not been elucidated. In this study, we investigated the etiology of ARHL in Apolipoprotein E (ApoE) deficient mice with diabetes and dyslipidemia. The atherosclerotic CD-STZ, WD-con, and WD-STZ mice respectively showed a 2.4-, 4.9-, and 6.8-fold larger area occupied by lesions throughout the aorta compared with the CD-con mice. A significantly larger area under the curve (AUC) was observed in the STZ-treated groups than in the non-treated groups based on the oral glucose tolerance test (OGTT). At 20 weeks of age, HbA1c levels were significantly higher in the CD-STZ and WD-STZ mice than in the CD-con and WD-con mice. In all the groups, the auditory brainstem response (ABR) thresholds of the 16-week-old mice were significantly higher compared to those of the 8-week-old mice. In particular, in the WD-STZ mice, the ABR thresholds of the left and right ears reached the maximum decibel peak equivalent sound pressure levels (130 dBpeSPL), which is a sign of deafness. The alterations in the ABR thresholds between the groups at the same age were significantly difference in both ears in the STZ-treated mice (CD-STZ, WD-STZ) and the CD-con mice. The apoptotic spiral ganglion neurons (SGNs) of the WD-STZ mice were significantly increased compared with the other three groups, indicating that SGN apoptosis resulted in hearing loss in STZ-induced diabetic ApoE KO mice fed with a WD. A significant loss of the stria vascularis cells was observed in the WD‑STZ group compared to the CD-con mice. In the organ of Corti, few apoptotic hair cells were found in all the groups; however, no significant difference was observed. Therefore, we consider that the reduced hearing ability in the STZ-treated and WD-fed groups was attributed to the damage to the SGN and stria vascularis in the cochlea. Thus, our results indicated that ototoxicity by diabetes and/or dyslipidemia accelerated the ARHL in ApoE KO mice, thereby suggesting the importance of appropriate treatment of patients with diabetes and/or dyslipidemia to prevent ARHL.